Investigating discovery strategies and pharmacological properties of stereodefined phosphorodithioate LNA gapmers - Jörg Duschmalé; Adrian Schäublin; Erik Funder; Steffen Schmidt; Łukasz J. Kiełpiński; Helle Nymark; Klaus Jensen; Troels Koch; Martina Duschmalé; Erich Koller; Marianne Ravn Møller; Simone Schadt; et al. (Elsevier, 2022)
The introduction of sulfur into the phosphate linkage of chemically synthesized oligonucleotides creates the stereocenters on phosphorus atoms. Researchers have valued the nature of backbone stereochemistry and early on investigated drug properties for the individual stereocenters in dimers or short oligomers. Only very recently, it has become possible to synthesize fully stereodefined antisense oligonucleotides in good yield and purity. Non-bridging phosphorodithioate (PS2) introduces second sulfur into the phosphorothioate linkage to remove the chirality of phosphorus atom. Here, we describe the application of symmetrical non-bridging PS2 linkages in the context of stereodefined locked nucleic acids (LNAs) antisense oligonucleotides with the goal of reducing chiral complexity and, ultimately, resulting in single molecules. In addition, we propose a rather simple strategy to rapidly identify stereodefined gapmers, combining PS2 and a preferred stereochemistry motif (RSSR), which supports RNase-H-mediated target knockdown. Pharmacological efficacy and metabolic stability are investigated systematically using ApoB as a target sequence, where in vivo data correlate well to what is observed in vitro.